Student Perception Toward The Function of Grammar in Speaking: Student's Perception Toward The Importance Grammar In Speaking - Tiara Sasmita; Ardiana (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2025)
Grammar plays a crucial role in enhancing speaking ability by providing a structural framework that ensures clear, logical, and organized communication. Mastery of grammar helps speakers construct grammatically correct sentences, thereby reducing ambiguity and improving overall fluency. This study aims to explore students' perspectives on the function of grammar in English-speaking proficiency, particularly among students in the English Language Education study program. A qualitative research method was employed, with data collected through structured interviews. The sample consisted of 20 students enrolled in the program. The findings indicate that the majority of students perceive grammar as essential in speaking, as it helps them avoid misunderstandings, build credibility as speakers, and boost their confidence. Overall, the study highlights the importance of grammar in effective communication, suggesting that a balanced approach to grammar instruction is necessary for developing both accuracy and fluency.Keywords; Students’ Perspective, Grammar, Speaking.